2016
DOI: 10.1002/jssc.201600704
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive two‐dimensional liquid chromatography for polyphenol analysis in foodstuffs

Abstract: Polyphenols are a class of plant secondary metabolites that are recently drawing a special interest because of their broad spectrum of pharmacological effects. As they are characterized by an enormous structural variability, the identification of these molecules in food samples is a difficult task, and sometimes having only a limited number of commercially available reference materials is not of great help. One-dimensional liquid chromatography is the most widely applied analytical approach for their analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 89 publications
(402 reference statements)
1
32
0
1
Order By: Relevance
“…Where applicable, we refer the reader to useful applications and reviews which offer a great deal additional information [63]. Applications in life sciences [64,65], food [66][67][68][69], polymers [70][71][72], and traditional Chinese medicine [73] are covered by recent reviews.…”
Section: Combining Selectivitiesmentioning
confidence: 99%
“…Where applicable, we refer the reader to useful applications and reviews which offer a great deal additional information [63]. Applications in life sciences [64,65], food [66][67][68][69], polymers [70][71][72], and traditional Chinese medicine [73] are covered by recent reviews.…”
Section: Combining Selectivitiesmentioning
confidence: 99%
“…As viable alternative for enhancing the overall separation capability, comprehensive 2D‐LC (LC × LC) has been far employed for phenol determination in many food and natural products as witnessed by several recent research and review articles [21–34]. It was already reported that LC × LC minimize matrix interferences at the detector, because of the higher resolving power, viz .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the traditional linear gradient, PE gradient provide a new modulation strategy for separation and cut the complex sample in 1st D [15]. According to the results of our previous work, the parameters of pulse width and step height play key role in PE gradient separation.…”
Section: Optimizing the First Dimensional Pe Gradientmentioning
confidence: 99%
“…However, due to the diverse structure and complex chemical composition of alkaloids, such 1D LC technology faces enormous challenges [11]. Comprehensive 2D LC (LC×LC) has attracted increasing attention in complex samples such as herb medicine, food additives, and so on for much higher peak capacity compared to 1D LC [12][13][14][15]. For dissociable compounds like alkaloids, they could be well separated by IEC, HILIC, normal phase LC (NPLC), and RPLC according to the difference in hydrophobicity and dissociation [16].…”
Section: Introductionmentioning
confidence: 99%